KAJIAN PENGEMBANGAN INFRASTRUKTUR TIK MENDUKUNG IMPLEMENTASI E-GOVERNMENT : STUDI KASUS BADAN LITBANG PERTANIAN - Gartina, Dhani (Informatika Pertanian, 2012)
Study on ICT i nfrastruct ure development e-governmen t implement ation: case study on Indonesi an Agency for Agricul tural Research and Development (IAARD). In line with government’s program t o perform good governa nce th rough the implement ation of e-gover nment, IAARD need to continually improve its public service, both internal and external organ izations by impr oving network uti lizati on of Infor mation and Communicati ons Technology (ICT) network. ICT network is the backbone in communicating data communications and information, so that its management and developmentneeds seriously at tention from all part ies. The con dition s of the development of ICT network infrastructures in IAARD have n et yet a cl ear dir ection and purpose, whil e the vision of IAARD becomes a worl d-cla ss research inst itute in 2014, therefore it needs that ICT plays role in the success of that vision. The draft of bl ueprin t for the development of ICT network infrastructures is hopeto be a real support in the success of that vision. A series of studies carried out was started by exexisting design each network units, the condition readiness ofinstitutions as well on technical implementing unit, Hum an Resources, up to polici es. After t hat data where evaluated in terms of the ability of the internaland external organizations. Based on the evaluation using SWOT analysis thereit was define the strategic plan to develop ICT infrastructures. Strategic Planconsist s of three m ain aspects of policy to develop ICT infrastructures; program; and the competency of human resources development program.